2022
DOI: 10.3390/cancers14071807
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of ATR, Chk1 and Wee1 Inhibitors with Olaparib Are Active in Olaparib Resistant Brca1 Proficient and Deficient Murine Ovarian Cells

Abstract: Background: Poly(ADP-ribose) polymerases inhibitor (PARPi) have shown clinical efficacy in ovarian carcinoma, especially in those harboring defects in homologous recombination (HR) repair, including BRCA1 and BRCA2 mutated tumors. There is increasing evidence however that PARPi resistance is common and develops through multiple mechanisms. Methods: ID8 F3 (HR proficient) and ID8 Brca1-/- (HR deficient) murine ovarian cells resistant to olaparib, a PARPi, were generated through stepwise drug concentrations in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…We further examined the hypothesis that olaparib cytotoxicity could be potentiated in both sensitive and resistant OC cell lines by the concurrent addition of either ATRi or CHK1i promoting blockage of the ATR/CHK1 pathway [ 17 , 20 , 43 ]. Specific concentrations of olaparib (0.5, 2.5, 5, and 10 μM), ATRi (0.5 μM), and CHK1i (2.5 μM) were selected to determine the lowest doses conferring synergistic cytotoxicity across the olaparib-sensitive cell lines without significant reduction in viability of PEO1-OR cells ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further examined the hypothesis that olaparib cytotoxicity could be potentiated in both sensitive and resistant OC cell lines by the concurrent addition of either ATRi or CHK1i promoting blockage of the ATR/CHK1 pathway [ 17 , 20 , 43 ]. Specific concentrations of olaparib (0.5, 2.5, 5, and 10 μM), ATRi (0.5 μM), and CHK1i (2.5 μM) were selected to determine the lowest doses conferring synergistic cytotoxicity across the olaparib-sensitive cell lines without significant reduction in viability of PEO1-OR cells ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for combination therapy is based on the concept that treatment with two or more agents with different molecular targets should induce a synergistic antitumor effect. Combinations of PARPi with inhibitors of the ATR/CHK1 pathway are under investigation for OC in vitro and in clinical trials for PARPi-naïve HGSOC patients and those who previously received PARPi [ 17 , 20 , 22 , 23 , 43 , 66 , 92 ]. However, further molecular studies are crucial to characterize the cellular response to this combination treatment in OC cells with distinct HR activities and resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BRCA1/BARD1 inhibits the advance of replications fork in an E3-independent manner. We can speculate that this is mediated by the interaction of BRCA1 with the checkpoint protein ATR (Chiappa et al, 2022). Consistently, PARP inhibitors-resistant tumors, including BRCA1/2-revertant tumors which do not reconstitute RAD51 foci formation and Cyclin E-amplified tumors, are sensitive to ATR inhibition (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Garcia and others (2017) found that adavosertib impairs HR and may work as a combination therapy with PARP inhibitor olaparib in BRCA1/2-mutant leukemias ( 46 ). Another study with HRD and HRP murine cell lines demonstrated that Wee1 inhibitor in combination with olaparib had no difference in effectiveness between the HR-deficient and -proficient cells ( 47 ). Both of these studies were performed in combination with PARP inhibitor olaparib.…”
Section: Discussionmentioning
confidence: 99%